(untitled) (Research, Society and Development, 2020)
Brazil is a country with great water availability. However, it also exposes conflicting situations of abundance and scarcity of water, and it is necessary for governments, users and civil society, better planning in the management of its use and in the solution to numerous conflicts that may arise. Therefore, this work aims to present cases of reported conflicts regarding water use in the state of Bahia, in the São Francisco River Basin (BHSF), specifically in the sub-basins of the Salitre River and the Verde and Jacaré Rivers. A bibliographic research was carried out that highlights several situations of conflicts in the studied region and suggestions for solutions for a better management of these situations involving different actors that can contribute to improve and define the demands of water in the regions. The São Francisco River basin is extensive and covers several states, in which it is observed that the main reason for the conflicts over water use is motivated especially in relation to productive and socioeconomic activities in the basins, with emphasis on agricultural activities, overexploitation of water resources, the excessive number of buses, among others. These conflicts presented indicate a lack of more effective measures so that management is able to solve the problems of the region and to provide the population involved with a better condition with regard to water resources.